CAPITAL MANAGEMENT OF UKRAINIAN AGRICULTURAL ENTERPRISES - PANCHENKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study revealed the relevance of capital management issues of Ukrainian agro-industrial complex enterprises in the context of ensuring their stable viability. The purpose of the study is to improve the methodological and applied principles of capital management of domestic enterprises of the agro-industrial complex in the situation of existing socio-economic instability. It is shown that the functioning of agrarian enterprises in the modern business environment, which served as a catalyst for institutional changes, is largely determined by the effective formation and use of capital of business entities, because in the conditions of war, the difficulty of accessing investment capital, the high cost of attracting permanent capital, and an acute shortage working capital of agricultural enterprises, as well as industrial processing of agricultural products, critically weakened the resource potential and ability of enterprises to survive in general. The regulation of the capital management strategy of agro-industrial complex enterprises has been developed as a management activity aimed at achieving the strategic goal of enterprises through the process of forming volumes, capital structure, sources of its financing and the cost of attracting funds and their effective use. The specifics, advantages, as well as key provisions of various types of capital management mechanisms of agro-industrial complex enterprises, in particular economic and economic, are substantiated. A system of forming the composition of policy tasks for the formation and use of capital of agribusiness enterprises is proposed in accordance with such strategic priorities as maximizing business profits, improving the investment attractiveness of the property complex of the agribusiness entity, ensuring the financial stability of the economic entity, expanding activities at the expense of own sources of working capital formation capital of the business entity. It was concluded that the optimization of the capital structure is one of the most important and difficult tasks that are solved in the process of financial management of agribusiness enterprises. At the same time, it is necessary to take into account the main features of each element of its composition.